The Macrophage-Osteoclast Axis in Osteoimmunity and Osteo-Related Diseases - Yao, Yao; Cai, Xiaoyu; Ren, Fujia; Ye, Yiqing; Wang, Fengmei; Zheng, Caihong; Qian, Ying; Zhang, Meng (Frontiers in Immunology, 2021)
Osteoimmunity is involved in regulating the balance of bone remodeling and resorption, and is essential for maintaining normal bone morphology. The interaction between immune cells and osteoclasts in the bone marrow or joint cavity is the basis of osteoimmunity, in which the macrophage-osteoclast axis plays a vital role. Monocytes or tissue-specific macrophages (macrophages resident in tissues) are an important origin of osteoclasts in inflammatory and immune environment. Although there are many reports on macrophages and osteoclasts, there is still a lack of systematic reviews on the macrophage-osteoclast axis in osteoimmunity. Elucidating the role of the macrophage-osteoclast axis in osteoimmunity is of great significance for the research or treatment of bone damage caused by inflammation and immune diseases. In this article, we introduced in detail the concept of osteoimmunity and the mechanism and regulators of the differentiation of macrophages into osteoclasts. Furthermore, we described the role of the macrophage-osteoclast axis in typical bone damage caused by inflammation and immune diseases. These provide a clear knowledge framework for studying macrophages and osteoclasts in inflammatory and immune environments. And targeting the macrophage-osteoclast axis may be an effective strategy to treat bone damage caused by inflammation and immune diseases.